Effects of Locomotion in Auditory Cortex Are Not Mediated by the VIP Network - Yavorska, Iryna; Wehr, Michael (Frontiers in Neural Circuits, 2021)
Movement has a prominent impact on activity in sensory cortex, but has opposing effects on visual and auditory cortex. Both cortical areas feature a VIP disinhibitory circuit, which in visual cortex contributes to the effect of running. In auditory cortex, however, the role of VIP circuitry in running effects remains poorly understood. Running and optogenetic VIP activation are known to differentially modulate sound-evoked activity in auditory cortex, but it is unknown how these effects vary across cortical layers, and whether laminar differences in the roles of VIP circuitry could contribute to the substantial diversity that has been observed in the effects of both movement and VIP activation. Here we asked whether VIP neurons contribute to the effects of running, across the layers of auditory cortex. We found that both running and optogenetic activation of VIP neurons produced diverse changes in the firing rates of auditory cortical neurons, but with distinct effects on spontaneous and evoked activity and with different patterns across cortical layers. On average, running increased spontaneous firing rates but decreased evoked firing rates, resulting in a reduction of the neuronal encoding of sound. This reduction in sound encoding was observed in all cortical layers, but was most pronounced in layer 2/3. In contrast, VIP activation increased both spontaneous and evoked firing rates, and had no net population-wide effect on sound encoding, but strongly suppressed sound encoding in layer 4 narrow-spiking neurons. These results suggest that VIP activation and running act independently, which we then tested by comparing the arithmetic sum of the two effects measured separately to the actual combined effect of running and VIP activation, which were closely matched. We conclude that the effects of locomotion in auditory cortex are not mediated by the VIP network.